In-situ infrared thermography measurements to master transmission laser welding process parameters of PEKK. (July 2018) - Villar, M.; Garnier, C.; Chabert, F.; Nassiet, V.; Samélor, D.; Diez, J.C.; Sotelo, A.; Madre, M.A.
Highlights: Transmission laser welding has been successfully performed on very high performance thermoplastic with tunable property (PEKK amorphous and semi-crystalline). Weldability of PEKK is demonstrated. The heat field is recorded during the welding experiment by infrared thermography with the camera sensor perpendicular to the welded interface and perpendicular to the side of the specimens. The feasibility of the temperature measurement at the interface is demonstrated. The evaluation of the impact of temperature variation due to the estimation of the emissivity factor is undertaken by a variability test. Abstract: The temperature field along the thickness of the specimens has been measured during transmission laser welding. Polyetherketoneketone (PEKK) is a very high performance thermoplastic with tunable properties. We have shown that this grade of PEKK can be turned to quasi-amorphous or semi-crystalline material, due to its slow kinetics of crystallization. Its glass transition temperature is 150 °C. The effect of its crystalline rate directly impacts its optical properties: the transmittance of quasi-amorphous PEKK is about 60% in the NIR region (wavelength range from 0.4 to 1.2 µm) whereas it is less than 3% for the semi-crystalline material. The welding tests have been carried out with an 808 nm laser diode apparatus. The heat field is recorded during the welding experiment by infrared thermography with the camera sensor perpendicular to the lasersheet and to the sample's length to focus on the welded interface. The study is divided in two steps: firstly, a single specimen is irradiated with an energy density of 22 J.mm − ²: the whole sample thickness is heated up, the maximum temperature reaches 222 ± 7 °C. This temperature corresponds to about Tg + 70 °C, but the polymer does not reach its melting temperature. After that, welding tests were performed: a transparent (quasi-amorphous) sample as the upper part and an opaque (semi-crystalline) one as the lower part were assembled in static conditions. The maximum temperature reached at the welded interface is about 295 °C when the upper specimen is irradiated for 16 s with an energy density of 28 J.mm − ². The temperature at the welded interface stays above Tg during 55 s and reached the melting temperature during 5 s before rapid cooling. These parameters are suitable to assemble both polymeric parts in a strong weld. This work shows that infrared thermography is an appropriate technique to improve the reliability of laser welding process of high performance thermoplastics.